Analysis of Digital HR Quality in Manpower and Transmigration of Karawang Regency - Syali Devita Ananda; Muhammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2025)
This study aims to analyze the factors of digital HR quality in human resource management at the Karawang Regency Department of Manpower and Transmigration to improve efficiency, effectiveness, and service quality. This research uses a quantitative descriptive method. The entire workforce of the Department of Manpower and Transmigration of Karawang Regency, consisting of 117 employees, serves as the population in this study, with a sample size of 105 respondents. Data were collected through questionnaires distributed to the respondents, with items assessed using a Likert scale. The data were tested for validity and reliability and analyzed using factor analysis with the help of SPSS 25. The study results indicated that the digital HR quality at the Karawang Regency Department of Manpower and Transmigration was generally good, with a total variance of 64.5%. From 15 indicators, five groups were formed with MSA values greater than 0.5, namely: training and development (14.5%), e-communication (14.2%), e-productivity (12.6%), digital competence (11.8%), and e-performance appraisal (11.2%).